Risk management framework : a lab-based approach to securing information systems - Broad, James (Syngress, an imprint of Elsevier, 2013)
Follows a fictitious organization through the risk management framework process, allowing the reader to follow the development of proper compliance measures such as FISMA and OMB requirements. Can also be tailored to meet other compliance requirements such as Payment Card Industry (PCI) or Sarbanes Oxley (SOX).